Variations in nitrogen use efficiency reflect the biochemical subtype while variations in water use efficiency reflect the evolutionary lineage of C4 grasses at inter‐glacial CO2. (21st December 2015) - Pinto, Harshini; Powell, Jeff R.; Sharwood, Robert E.; Tissue, David T.; Ghannoum, Oula
Abstract: C4 photosynthesis evolved multiple times in diverse lineages. Most physiological studies comparing C4 plants were not conducted at the low atmospheric CO2 prevailing during their evolution. Here, 24 C4 grasses belonging to three biochemical subtypes [nicotinamide adenine dinucleotide malic enzyme (NAD‐ME), phosphoenolpyruvate carboxykinase (PCK) and nicotinamide adenine dinucleotide phosphate malic enzyme (NADP‐ME)] and six major evolutionary lineages were grown under ambient (400 μ L L −1 ) and inter‐glacial (280 μ L L −1 ) CO2 . We hypothesized that nitrogen‐related and water‐related physiological traits are associated with subtypes and lineages, respectively. Photosynthetic rate and stomatal conductance were constrained by the shared lineage, while variation in leaf mass per area (LMA), leaf N per area, plant dry mass and plant water use efficiency were influenced by the subtype. Subtype and lineage were equally important for explaining variations in photosynthetic nitrogen use efficiency (PNUE) and photosynthetic water use efficiency (PWUE). CO2 treatment impacted most parameters. Overall, higher LMA and leaf N distinguished the Chloridoideae/NAD‐ME group, while NADP‐ME and PCK grasses were distinguished by higher PNUE regardless of lineage. Plants were characterized by high photosynthesis and PWUE when grown at ambient CO2 and by high conductance at inter‐glacial CO2 . In conclusion, the evolutionary and biochemical diversity among C4 grasses was aligned with discernible leaf physiology, but it remains unknown whether these traits represent ecophysiological adaptation. Abstract : Using diverse C4 grasses grown at ambient and inter‐glacial CO2, this study demonstrated that variations in photosynthetic nitrogen use efficiency (driven by leaf mass per area and leaf N) were most likely related to the C4 biochemical subtype, while variations in photosynthetic water use efficiency (driven by stomatal conductance) were related to the C4 lineage and reflected species adaptation to soil aridity.